Determination of Biologically Active Compounds and Antioxidant Capacity In Vitro in Fruit of Small Cranberries (Vaccinium oxycoccos L.) Growing in Natural Habitats in Lithuania - Mindaugas Liaudanskas; Rima Šedbarė; Valdimaras Janulis (MDPI AG, 2024)
The composition of flavonols, proanthocyanidins, anthocyanins, triterpene compounds, and chlorogenic acid in small cranberry fruit samples collected in natural habitats in Lithuania and variation in the antioxidant capacity of cranberry fruit extracts was determined. This study showed that in the flavonol group, hyperoside and myricetin-3-O-galactoside predominated in cranberry fruit samples; in the anthocyanin group, the predominant compounds were cyanidin-3-O-galactoside, cyanidin-3-O-arabinoside, peonidin-3-O-galactoside, and peonidin-3-O-arabinoside, and in the group of triterpene compounds, ursolic acid was predominant. The highest total amounts of flavonols and anthocyanins were found in the samples collected in Čepkeliai State Strict Nature Reserve (2079.44 ± 102.99 μg/g and 6993.79 ± 350.22 μg/g, respectively). Cluster analysis of the chemical composition of small cranberry fruit samples revealed trends in the accumulation of bioactive compounds in cranberry fruit. Cranberry fruit samples collected in central Lithuania had higher levels of triterpene compounds. Statistical correlation analysis showed the strongest correlation between the quantitative composition of cyanidin-3-O-arabinoside and peonidin-3-O-arabinoside and the reducing capacity of the ethanolic extracts of the cranberry fruit samples assessed in vitro by the FRAP assay (r = 0.882, p < 0.01 and r = 0.805, p < 0.01, respectively). Summarizing the results, the geographical factor affects the variation of the quantitative composition of biologically active compounds in cranberry fruit samples.